(untitled) (Journal of Universal Science Research, 2023)
In this article, we discuss the Role of Conceptual Metaphor in Literary Translation. The role of conceptual metaphor in literary translation is significant because it allows for the translation of complex language and ideas across different languages. Conceptual metaphors provide a way to convey abstract or difficult concepts in a more accessible way, and translators must be able to identify and understand these metaphorical expressions in order to accurately convey the same meaning in the target language. In literary translation, conceptual metaphors can also contribute to the overall style and tone of the text, and translators must consider these elements in their translations.